Hubungan Lama Penggunaan Gadget dengan Gangguan Pola Tidur pada Anak Sekolah Dasar Kelas 4 Sampai 6 di Denpasar - Sagung Putri Permana Lestari MP; I Ketut Tangking Widarsa; A. A. Ayumi Witantri (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Gadgets are one of the most favored technological advancements by people of all ages, including elementary school student. Gadget can cause negative impacts if used at a long duration of time, which is sleeping disorders. This research studies about the Correlation of Gadget Usage Duration with Sleeping Disorders of 4th until 6th Grade Elementary School Student in Denpasar. This research used an analytical correlation and cross-sectional design. Subjects used was every 4th until 6th grade elementary school student in Denpasar who fit the criteria. The time of the research started from September 2021 until May 2022 using purposive sampling as the data gathering technique as well as questionnaire as the research instrument. Data analysis uses univariate frequency distribution and bivariate chi-square analysis. Final results of the bivariate shows that the p value is 0,00 with score of r = 0,4 (correlation coefficient), explains that the variable linear correlation value of gadget usage duration with sleeping disorders have a positive correlation and have low connection. Based off the correlation value results, the determinant coefficient value is (r 2 = 0,16). This shows that the gadget usage duration variable affects 16% of sleeping disorders, while the 84% are affected by other factors that are non available within a research model.